The Kidfluencer Phenomenon and Modern Slavery: A Critical Analysis of Indonesia's Legal Framework in Protecting Children from Digital Exploitation - Lubis, Alvan Rahfiansyah (Arkus, 2025)
The digital era has ushered in unprecedented opportunities for children to engage with online platforms. However, this increased accessibility has also exposed them to new forms of exploitation, including the "kidfluencer" phenomenon. This study examines the legal framework in Indonesia concerning child digital exploitation, focusing on the adequacy of existing laws in protecting children involved in the creation of digital content for commercial purposes. This research employed a qualitative legal research methodology. It involved a comprehensive review of relevant national legislation, international legal instruments, academic literature, and reports from governmental and non-governmental organizations. A comparative analysis was conducted to assess the alignment of Indonesian laws with international standards for child protection. The study revealed that while Indonesia has ratified international conventions and enacted laws related to child protection, gaps exist in addressing the specific nuances of digital exploitation. Existing laws primarily focus on traditional forms of child labor and abuse, lacking explicit provisions for online exploitation, particularly within the context of the kidfluencer phenomenon. In conclusion, this research highlights the urgent need for Indonesia to strengthen its legal framework to specifically address the exploitation of children in the digital realm. Recommendations include amending existing laws to include explicit provisions on digital exploitation, enhancing law enforcement capacity, raising public awareness, and fostering collaboration between stakeholders such as the government, digital platforms, and civil society organizations.